Studi Perancangan Material Komposit Berbahan Dasar Kitosan dan Selulosa Sebagai Langkah Pengendalian Limbah Tekstil Methylene Blue - Budiman, Yosef; Putra, Eka Rahmat; Lestari, Ajeng Yulianti Dwi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The amount of methylene blue (MB) in water bodies is one of the environmental issues that still need to be considered. The vast concentration of MB may increase the chemical oxygen demand level, so it has the potential to disrupt aquatic ecosystems. On the other hand, the adsorption process is one of the best methods that functionalizes as a utility for dye removal. This research studied the MB adsorption characteristic using cellulose-based adsorbent from banana fronds. Adsorbents were synthesized and modified using chitosan, bentonite, and acid addition. The adsorption process occurred at various concentrations of MB (40, 60, 80, 100, and 120 ppm) then the result will be proved and calculated by analysis using UV Vis and FTIR Spectrophotometer. The result showed that the bentonite addition could not increase the adsorption capacity optimally due to fluctuating spectrum of UV-Vis. In conclusion, the adsorbent can absorb MB in wastewater which is the optimal condition at 80 ppm for 24 hours.